The Implementation of Wadiah Contracts in Islamic Banking: Safeguarding Customer Confidentiality and Institutional Trust - Putri Ramadani Massora; Kateryna Shevchenko (PT. Islamic Research Publisher, 2024)
This study examines the implementation of the Wadiah contract in Islamic banking, with particular emphasis on the protection of customer data confidentiality and its conformity with Sharia principles and the regulatory framework established under Law No. 4 of 2023 on the Development and Strengthening of the Financial Sector (P2SK Law). Within Islamic banking, the Wadiah contract embodies a fiduciary relationship that requires Islamic financial institutions to safeguard not only customers’ deposited funds but also the confidentiality of their personal and financial information. This research employs a normative legal approach, utilizing statutory, conceptual, and comparative analyses. Data were collected through an extensive review of relevant legal instruments, including DSN-MUI Fatwa No. 02/DSN-MUI/IV/2000 on Wadiah savings, Islamic banking regulations, and the provisions of the P2SK Law concerning consumer and data protection. The findings reveal that the Wadiah contract creates both legal and ethical obligations for Islamic banks to maintain customer confidentiality as an integral manifestation of the trust (amanah) principle embedded in Islamic commercial law. Furthermore, the P2SK Law strengthens this obligation by providing a more comprehensive framework for customer data protection and establishing legal consequences for violations of confidentiality. The study argues that effective implementation of the Wadiah contract contributes not only to regulatory compliance but also to the realization of the objectives of Islamic law (maqāṣid al-sharīʿah), particularly the protection of wealth (ḥifẓ al-māl) and human dignity (ḥifẓ al-ʿirḍ). Academically, this research contributes to the growing discourse on the intersection between Islamic contract law, financial governance, and data protection by positioning customer confidentiality as a substantive dimension of Wadiah rather than merely an administrative obligation. Strengthening this perspective is essential for enhancing public trust and promoting sustainable development within the Islamic banking sector.